Meaningful Productivity Strategy: The Key to Reducing Poverty In The 3T Region of The Mentawai Islands - Sabagalet, Yudas; Zulfa, Zulfa; Febrianto, Hary; Yatim, Yenita (Universitas PGRI Sumatera Barat, 2025)
The Mentawai Islands, as one of Indonesia's Frontier, Outermost, and Disadvantaged (3T) regions, face the challenge of structural poverty that contradicts its rich natural resources. This study aims to formulate the concept of